Leitura recreativa na escola de 1º grau da rede oficial municipal de ensino de Belo Horizonte - Maria Helena de Andrade Magalhães (1980)
Study about recreational reading in first-grade municipal schools of the official school network of Belo Horizonte to obtain information about the preferences of leisure and reading of students; books access facilities provided by the school; activities developed by teachers and librarians to stimulate recreational reading. Questionnaires were administered to 660 fifth to eighth grade students, and to 45 Portuguese language teachers. Eight school librarians were interviewed. The following results were obtained: a) Reading is not the first option among the leisure activities of students; b) Students prefer books containing adventure tales and love stories; c) the Portuguese language teacher gives students a list of books to read, and develops some activities to verify this reading; d) the performance of the school libraries concerning recreational reading was considered inadequate. Other surveys are suggested, approaching different aspects of the subject.